2022
DOI: 10.1007/s00330-022-09083-w
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions of radiologists towards online (virtual) oncologic multidisciplinary team meetings during the COVID-19 pandemic—a survey of the European Society of Oncologic Imaging (ESOI)

Abstract: Objectives To explore radiologists’ opinions regarding the shift from in-person oncologic multidisciplinary team meetings (MDTMs) to online MDTMs. To assess the perceived impact of online MDTMs, and to evaluate clinical and technical aspects of online meetings. Methods An online questionnaire including 24 questions was e-mailed to all European Society of Oncologic Imaging (ESOI) members. Questions targeted the structure and efficacy of online MDTMs, including benefits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…We discovered a total of 36 papers using our search criteria. The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…We discovered a total of 36 papers using our search criteria. The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Attendance. The foremost benefit of the virtual nature of VMDTMs has been the removed need to schedule rooms for the meeting, thereby facilitating convenient remote access for participants [19,43]. This benefits the meeting itself by impacting clinician attendance as, since the advent of the virtual format, participant attendance in board meetings has reportedly increased [19,43,44].…”
Section: 2a Organizationmentioning
confidence: 99%
See 3 more Smart Citations